Pola Rugae Palatina pada Populasi Osing - Eko Prastyo; Ledy Ana Zulfatunnadiroh; Sharly Delineria Marlion Nirbita (Jurnal Keperawatan Silampari, 2020)
This study aims to describe the palatal rugae pattern based on the Kapali classification in the Osing population. The research method used in this research is descriptive observational. The results showed that the simple frequency distribution of the palatine rugae pattern in the Osing population was 45.6% curved, 28.3% wavy, 8.7% circular, and 17.4% straight. In conclusion, the variation in the palatine rugae based on the Kapali classification can be shown from this study's results on the Osing population. Keywords: Kapali Classification, Forensic Odontology, Osing Population, Rugae Palatina